Comparison of effects of different dietary interventions on cognitive function in Alzheimer’s disease: protocol for systematic review and network meta-analysis - Lili Chen (BMJ Publishing Group, 2021)
Introduction Alzheimer’s disease (AD) is the most common neurodegenerative disease and is characterised by cognitive impairment. Non-pharmacological treatments such as diet therapy have been widely investigated in studies on AD. Given the synergistic effects of nutrients present in foods, considering overall dietary composition rather than focusing on a single nutrient may be more useful for evaluating the relationship between diet and AD cognition. The present study aimed to assess the efficacy of different dietary interventions (eg, ketogenic and Mediterranean diets) on cognitive function in patients with AD in a systematic review and pairwise and network meta-analyses of randomised controlled trials or clinical trials.Methods and analysis Two reviewers will independently conduct searches of PubMed, Cochrane Central Register of Controlled Trials, Embase, CINAHL, PsycINFO and China National Knowledge Infrastructure databases. Data will be extracted from selected studies and risk of bias will be assessed using the revised Cochrane risk-of-bias tool, and evidence quality will be assessed according to the Grading of Recommendations, Assessment, Development and Evaluation framework. The primary outcome of interest is cognitive function in patients with AD; secondary outcomes include biochemical biomarkers of AD and oxidative stress and/or inﬂammatory biomarkers in cerebrospinal fluid or plasma. For each outcome, random-effects pairwise and network meta-analyses will be carried out to determine the pooled relative effect of each intervention relative to every other intervention.Ethics and dissemination As this study is based solely on published literature, no ethics approval is required. The research will be published in a peer-reviewed journal.